Using the Place Mat Technique to improve writing skills - Ida Muliawati (English Education Journal, 2016)
This research was to find out whether teaching descriptive writing by using the Place Mat technique would be effective to improve the writing skills of students and to find out their responses to the implementation of this technique. The sample for this research was 56 students from the first grade at SMAN 4 Banda Aceh in the academic year 2014/2015. A true experimental design was used in this research in which two classes were selected at random, one to be the experimental class, and the other the control class. The instruments used to collect the data were tests and a questionnaire. There were two steps in collecting the test data, namely the pre-test and the post-test. To get the students’ responses to the implementation of this technique, a questionnaire was used. The results revealed that there was a significant difference in achievement in writing descriptive texts between the students who were taught using this technique and those who were taught by using the individual writing activity. This was proven by the score from the t-test on the post-test which was 3.27 that was higher than the t-table score which was only 1.684. Furthermore, based on the result from the questionnaire, the students responded positively toward the use of this technique for teaching writing.